APLIKASI PUPUK ORGANIK CAIR (POC) TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN SELADA (Lactuca sativa L.) PADA JARAK TANAM YANG BERBEDA - Hardian Indra Guna; Armaini Armaini; Fifi Puspita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This study aims to determine the effect of concentration of liquid organic fertilizer and determine the concentration of liquid organic fertilizer is best for growth and production of lettuce plants at different spacing. The experiment was conducted in experimental garden of Faculty of Agriculture, University of Riau on March 2017 until May 2017. This experiment was conducted experimentally by using Randomized Plot Design with Randomized Block Design consisting of 3 levels of spacing, namely: J1 = 15 cm x 15 cm, J2 = 20 cm x 20 cm, J3 = 25 cm x 25 cm, and liquid organic fertilizer consisting of 4 levels, namely: P1 = Without the application of liquid organic fertilizer, P2 = 1 ml/l water, P3 = 2 ml/l water, P4 = 3 ml/l water. The parameters observed were plant height, number of leaves, total weight of plant, consumption weight of plant, crown dry weight, root dry weight and dry weight of plant. The data obtained were analyzed statistically with fingerprint and then tested further with DNMRT at 5% level. Provision of liquid organic fertilizer affect the growth of lettuce plants and the application of liquid organic fertilizer concentration of 3 ml/l of water at plant spacing of 25 cm x 25 cm showed the best results in improving the growth and production of lettuce. Keywords : organic liquid fertilizer, plant spacing, lettuce